Uji Efektivitas Prosedur Disinfeksi Tingkat Tinggi Endoskopi Saluran Cerna RSUD Dr. Moewardi - Ramadhani, Aviaddina; Marwoto, .; Saptawati, Leli (Nexus Biomedika, 2013)
Background: The risk of infection associated with gastrointestinal endoscope remains a topic of interest. This vexation may be related to reliability of the disinfecting techniques or the compliances with the guideline laid down for high-level disinfection. Gastrointestinal endoscope disinfecting techniques may vary from site to site. This study was to examine the effectiveness of gastrointestinal endoscope high-level disinfection at Rumah Sakit Umum Daerah (RSUD) Dr. Moewardi. Methods: An observational study using cross sectional design was conducted at RSUD Dr. Moewardi. Thirty samples from gastrointestinal endoscope swab after high-level disinfection process with 24 hours storage and without storage was sampled with convenience sampling technique. Data from this research were analyzed descriptively and tested using Chi square test. Results: Microorganism were detected in 11/14 samples of gastrointestinal endoscope after 24 hours storage and 3/16 samples of gastrointestinal endoscope without storage process. The microorganisms were Bacillus sp, Staphylococcus aureus, Staphylococcus non-aureus, and Clostridium sp. Significant relationship was detected between storage processes after gastrointestinal endoscope high-level disinfection with microorganism contamination. Conclusions: High-level disinfection of gastrointestinal endoscopes RSUD Dr. Moewardi was not yet effective. There was a significant relationship between gastrointestinal endoscopy storage for 24 hours with the effectiveness of high-level disinfection of gastrointestinal endoscopes. Keywords: high-level disinfection, gastrointestinal endoscope, 24 hours storage, without 24 hours storage.